PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI FLOW DISTRO PREMBUN (STIE Rajawali Purworejo, 2021)
Service quality is the main milestone in the company's running activities. In general, providing good and maximum service will encourage consumers to make purchasing decisions. This has a very good impact on the company's goal, namely to increase sales output. The aim of this research is to determine